Legal Protections to Promote Response Willingness Among the Local Public Health Workforce. (26th February 2015) - Rutkow, Lainie; Vernick, Jon S.; Thompson, Carol B.; Piltch-Loeb, Rachael; Barnett, Daniel J.
Abstract: Objective: The legal environment may improve response willingness among local health department (LHD) workers. We examined whether 3 hypothetical legal protections influence LHD workers' self-reported response willingness for 4 emergency scenarios and whether specific demographic factors are associated with LHD workers' response willingness given these legal protections. Methods: Our 2011–2012 survey included questions on demographics and about attitudes and beliefs regarding LHD workers' willingness to respond to 4 emergency scenarios given specific legal protections (i.e., ensuring priority health care for workers' families, granting workers access to mental health services, and guaranteeing access to personal protective equipment). Data were collected from 1238 LHD workers in 3 states. Results: Across scenarios, between 60% and 83% of LHD workers agreed that they would be more willing to respond given the presence of 1 of the 3 hypothetical legal protections. Among the 3 legal protections, a guarantee of personal protective equipment elicited the greatest agreement with improved response willingness. Conclusions: Specific legal protections augment a majority of LHD workers' response willingness. Policymakers must, however, balance improved response willingness with other considerations, such as the ethical implications of prioritizing responders over the general public. ( Disaster Med Public Health Preparedness . 2015;9:98–102)